Village Project as the Implementation of the Program of Freedom to Learn-Independent Campus (Merdeka Belajar-Kampus Merdeka) in Geography Education Program - Mariya, Sri; Gistituatuti, Nurhizrah; Betri, Alwen (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
ABSTRACT: The village project is one part of the Thematic Community Service Program of Freedom to Learn-Independent Campus program or in Bahasa Indonesia called as Merdeka Belajar – Kampus Merdeka (MBKM) which is a form of education by providing students with experience to live in a society in outside the university, by which with the community can identify potentials of the problems and solve it together. With this activity, students are expected to be able to develop the potential of the village/district and provide solutions to the problems that exist in the that area. This type of research is qualitative research, with data collection methods with observation and documentation. This research was conducted in three villages in West Sumatra, namely Nagari Mandeh, Nagari Manggopoh and Nagari Sungai Pua. In this program, there are seven stages of activities carried out, namely student socialization, technical focus group discussion (FGD), student debriefing, socialization in the village, Geographic Information System (GIS) training, and Web GIS training in Nagari Mandeh, Nagari Manggopoh, and Nagari Sungai Pua. The activity focused on two important programs, namely GIS training and village website training. The results of this program are village maps and websites, there are thirteen (13) physical maps of the area and twelve (12) regional social maps and digital data collection, the results of which are then converted into the equivalent of 10 courses converted for a total of 20 credits.